Níveis de ansiedade, depressão e engagement no trabalho em residentes de pediatria - Teixeira, Priscila Regina (2016)
The medical residency is a teaching mode characterized by in-service training under supervision at all times. Comprises an intense and thorough work experience, makes professionals a group at risk for developing emotional disorders and dysfunctions, professionals with high incidence of anxiety and depression. Despite causing harmful effects on sensitivity of doctors in relation to patients, in the academic and professional performance, health, well-being and quality of life, contributes to enhancing skills, self-confidence and security professionals. Objectives: To evaluate the levels of anxiety, depression and work engagement in professionals enrolled in a Residency Program in Pediatrics of an educational institution in the State of São Paulo in Brazil. Methods: Cross-sectional study of population base, among the professionals enrolled in the medical residency program in Pediatrics. The data were collected between the months of november, 2013 to february, 2014, using instruments: an elaborate by the authors, for Demographic data collection, the Beck Anxiety Scale (BAI), the Beck Depression Scale (BDI-II) and the Utrecht Work Engagement Scale (UWES). Results: 36 residents participated in the study. There was a predominance of females (91.4%), median age 28 years (minimum: 25; maximum: 34), singles (86.11%), family income from 10 or more wages (47.1%), workday of 12 hours or more (55.6%), without physical activity (55.5%) and leisure (44.2%), with another employment (71.4%) satisfied with the job (88.9%) and thought about quitting the programme (52.8%). The engagement ranged from 3.56 to 4.28. The dimension Dedication obtained high index (4.28 ± 1.12) and dimensions, Force Absorption and Engagement, (3.58 ± 3.56 ± 0.98 1.00; and 3.78 ± 0.96). Anxiety was present in 50.0% and depression in 44.4%. There was no statistical association of anxiety with the age group (p<0.005) and with the desire to give up the program (p=0.038); and depression with age group (p=0.001), practice of physical activity (p=0.016), leisure activities (p=0.012) and with the desire to give up the program (p=0.008). Conclusions: The residents showed good levels of engagement, especially in the field Dedication. There is a low percentage of people with low level of engagement in all areas of the UWES. Anxiety and depression levels were higher than those observed in other programs, with Association of these disorders with age, lack of physical activity and leisure, highlighting the need for greater attention and professional support, and implementation of control of stressors factors among residents in Pediatrics, and of strategies to promote physical and mental well-being of these professionals.